EFEKTIVITAS PEMUNGUTAN RETRIBUSI RUANG MILIK JALAN (RUMIJA) UNTUK MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN BOGOR - Tuti Tirwaningsih (Magister Hukum Sekolah Pascasarjana Unida, 2016)
The Government of Bogor Regency make charges for Services as one of the revenue sources of local revenue to meet the needs of government spending and regional development. The type of retribution for business service is retribution use of Regional assets, with the object is the use of right of way (ROW). Identification of problems in this study include the implementation of retribution Rumija, obstacles in its implementation, and effectiveness of picking retribution of Rumija for increase revenue. The research method used is normative juridical and sociological juridical approach method (empirical) to know the implication of Local Regulation Number 29 Year 2011 about Retribution of Business Service to increasing acceptance of Bogor Regency local revenue. Although the type of retribution, retribution object, structure and amount of retribution fare, procedure of payment of retribution, administrative sanction, expiry, and criminal provision have been regulated in Local Regulation Number 29 of 2011 on Business Service retribution, but in its management still not effective due to some Obstacles both internal and external, so to optimize the collection of ROW retribution then the Regional Government Bogor Regency should make some efforts both internal and external to the realization of revenue from the original revenue ROW retribution sector increased.